Interactive-Based Academic Writing Instruction: A Model for Improving Students’ Writing Competence - Abdul Rahman R.; Aswar Aswar (Jurnal Ilmiah Multidisiplin Amsir, 2026)
This study investigates the implementation of an interactive-based instructional model in teaching academic writing and its contribution to improving students’ writing competence in higher education. Academic writing has become an essential skill for university students, particularly in responding to the demands of scholarly communication and academic publication. However, many students still encounter difficulties in organizing ideas, developing arguments, maintaining coherence, and applying appropriate academic conventions. Traditional teacher-centered approaches are often considered less effective in fostering active engagement and critical thinking during the writing process. Therefore, this study proposes an interactive-based academic writing instruction model that emphasizes collaboration, discussion, feedback exchange, and active student participation. This research employed a qualitative descriptive approach involving university students enrolled in an Academic Writing course. Data were collected through classroom observations, interviews, documentation, and analysis of students’ writing performances. The findings indicate that the interactive-based instructional model significantly enhanced students’ engagement, confidence, and writing competence. Students demonstrated improvements in idea development, organization, academic vocabulary, grammatical accuracy, and critical argumentation. Furthermore, collaborative interaction between students and lecturers created a more supportive and reflective learning environment. The study concludes that interactive-based academic writing instruction provides an effective pedagogical framework for improving students’ academic writing competence and promoting active learning in higher education contexts.